Нормативна база, сучасний стан та заходи з покращання якості українського вугілля - Lyashenko O.F.; Perov M.O. (General Energy Institute of the National Academy of Sciences of Ukraine, 2004)
The condition of normative base concerning quality of coal production is analyzed. The estimation of the basic parameters of quality of the Ukrainian coal is executed and actions on their improvement are determined.